2014
DOI: 10.1177/0284185114560210
|View full text |Cite
|
Sign up to set email alerts
|

Role of low dose CT angiography in the follow-up after endovascular aneurysm repair of abdominal aorta

Abstract: The 100 kV protocol allowed a consistent RD reduction, maintaining a satisfactory image quality in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…To address this issue, low-dose CTA protocols have been reported to show the feasibility of reducing both radiation dose (reduce tube voltage from 120 to 100 or 80 kV) and contrast volume (lower contrast medium to 30 mL) while capturing diagnostic-quality images. [46][47][48] Another strategy to solve this issue is to use duplex ultrasound as an alternative to CTA in the follow-up of EVAR patients. Several authors have shown that contrast-enhanced ultrasound is as accurate as or better than CTA in detecting endoleaks, monitoring aneurysm dimensional changes, and assessing stented vessel patency by analyzing hemodynamic flow to the renal arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, low-dose CTA protocols have been reported to show the feasibility of reducing both radiation dose (reduce tube voltage from 120 to 100 or 80 kV) and contrast volume (lower contrast medium to 30 mL) while capturing diagnostic-quality images. [46][47][48] Another strategy to solve this issue is to use duplex ultrasound as an alternative to CTA in the follow-up of EVAR patients. Several authors have shown that contrast-enhanced ultrasound is as accurate as or better than CTA in detecting endoleaks, monitoring aneurysm dimensional changes, and assessing stented vessel patency by analyzing hemodynamic flow to the renal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, low-dose CTA protocols have been reported to show the feasibility of reducing both radiation dose (reduce tube voltage from 120 to 100 or 80 kV) and contrast volume (lower contrast medium to 30 mL) while capturing diagnostic-quality images. 4648…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound and low-dose CTA have gained popularity and may offer a safe and accurate imaging alternative in postoperative evaluation of EVAR patients. [49][50][51][52] Additionally, all organizations except JCS 15 and NICE 17 recommend surveillance imaging after open repair at 5-year intervals ( Table 5).…”
Section: Follow-up After Aaa Repair and Endoleak Treatmentmentioning
confidence: 99%
“…Patients receiving EVAR undergo regular imaging followup to check the patency of arteries and the diameter of aortic aneurysms, and to determine whether the aortic aneurysms are completely excluded from the systemic circulation, and whether the stent grafts are deployed properly in relation to the renal and other visceral arteries. Among various imaging modalities, computed tomography angiography (CTA) is the preferred imaging technique for postoperative follow-up of EVAR, with low-dose CTA protocols reported to reduce cumulative radiation dose (12)(13)(14)(15). With improvements in computed tomography (CT) scanning techniques, the spatial resolution of latest multi-detector row CT scanners is between 230 and 500 μm, which enables accurate assessment of anatomical structures and pathologies such as coronary arteries and plaque features (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%